Impact of Fe2+ and Shear Stress on the Development and Mesoscopic Structure of Biofilms—A Bacillus subtilis Case Study - Luisa Gierl; Harald Horn; Michael Wagner (Microorganisms, 2022)
Bivalent cations are known to affect the structural and mechanical properties of biofilms. In order to reveal the impact of Fe2+ ions within the cultivation medium on biofilm development, structure and stability, Bacillus subtilis biofilms were cultivated in mini-fluidic flow cells. Two different Fe2+ inflow concentrations (0.25 and 2.5 mg/L, respectively) and wall shear stress levels (0.05 and 0.27 Pa, respectively) were tested. Mesoscopic biofilm structure was determined daily in situ and non-invasively by means of optical coherence tomography. A set of ten structural parameters was used to quantify biofilm structure, its development and change. The study focused on characterizing biofilm structure and development at the mesoscale (mm-range). Therefore, biofilm replicates (n = 10) were cultivated and analyzed. Three hypotheses were defined in order to estimate the effect of Fe2+ inflow concentration and/or wall shear stress on biofilm development and structure, respectively. It was not the intention to investigate and describe the underlying mechanisms of iron incorporation as this would require a different set of tools applied at microscopic levels as well as the use of, i.e., omic approaches. Fe2+ addition influenced biofilm development (e.g., biofilm accumulation) and structure markedly. Experiments revealed the accumulation of FeO(OH) within the biofilm matrix and a positive correlation of Fe2+ inflow concentration and biofilm accumulation. In more detail, independent of the wall shear stress applied during cultivation, biofilms grew approximately four times thicker at 2.5 mg Fe2+/L (44.8 µmol/L; high inflow concentration) compared to the low Fe2+ inflow concentration of 0.25 mg Fe2+/L (4.48 µmol/L). This finding was statistically verified (Scheirer–Ray–Hare test, ANOVA) and hints at a higher stability of Bacillus subtilis biofilms (e.g., elevated cohesive and adhesive strength) when grown at elevated Fe2+ inflow concentrations.